Quantification of the vocal folds' dynamic displacements. (24th March 2016) - Hernández-Montes, María del Socorro; Muñoz, Silvino; De La Torre, Manuel; Flores, Mauricio; Pérez, Carlos; Mendoza-Santoyo, Fernando
Abstract: Fast dynamic data acquisition techniques are required to investigate the motional behavior of the vocal folds (VFs) when they are subjected to a steady air-flow through the trachea. High-speed digital holographic interferometry (DHI) is a non-invasive full-field-of-view technique that has proved its usefulness to study rapid and non-repetitive object movements. Hence it is an ideal technique used here to measure VF displacements and vibration patterns at 2000 fps. Analyses from a set of 200 displacement images showed that VFs' vibration cycles are established along their width ( y ) and length ( x ). Furthermore, the maximum deformation for the right and left VFs' area may be quantified from these images, which in itself represents an important result in the characterization of this structure. At a controlled air pressure, VF displacements fall within the range ~100–1740 nm, with a calculated precision and accuracy that yields a variation coefficient of 1.91%. High-speed acquisition of full-field images of VFs and their displacement quantification are on their own significant data in the study of their functional and physiological behavior since voice quality and production depend on how they vibrate, i.e. their displacement amplitude and frequency. Additionally, the use of high speed DHI avoids prolonged examinations and represents a significant scientific and technological alternative contribution in advancing the knowledge and working mechanisms of these tissues.